‘Sense of belonging’: The influence of individual factors in the learning environment of South African interns - K Naidoo; J van Wyk; M Adhikari (South African Medical Association, 2018)
Background. The focus is usually on organisational issues when reporting factors influencing the perceptions of South African (SA) medical interns regarding their learning environment (LE). Individual demographic factors are now being recognised as equally important in influencing these perceptions.Objective. To determine whether individual demographic factors influence interns’ perceptions of the LE during their paediatrics rotation in hospitals burdened with high disease in SA.Methods. Perceptions of the LE among interns in KwaZulu-Natal, SA, were assessed in December 2015, using a validated version of the Postgraduate Hospital Educational Environmental Measure (PHEEM). Overall and subscale PHEEM scores were calculated using Likert scales. The association of these scores with various sociocultural factors relevant to the SA context, previous educational exposure and year of internship were examined using ANOVA or Student t-tests.Results. A total of 209 interns (59.3%) was sampled. The ethnic breakdown of sampled interns reflected the changing demographic profile of SA junior doctors. Statistically significant associations of overall and teaching subscale PHEEM scores were found with ethnicity (p=0.024), urban/rural status (p=0.023), year of internship (p=0.0047) and university origin (p=0.015). These factors corroborated characteristics that reflect both past disadvantage in the SA context, and those of being an ‘outsider’ in an established group.Conclusions. Intern training programmes in SA need to recognise that individual demographic factors influence interns’ perceptions in the context of teaching and mentoring in a discipline. With rapid changes in the demographic profiles of junior doctors, SA intern trainers need to enable a ‘sense of belonging’ in LEs.